Differentiation of Mesenchymal Stem Cells Derived from Embryonic Umbilical Cord Blood (UCB-MSCs) Into Fibroblastic Lineage for Use as Skin Grafts in Trinidad and Tobago - Ramlachan, Nicole; Foster, Jerome (British Journal of Healthcare and Medical Research, 2024)
The application of stem cells to medical therapies for example regenerative medicine and tissue engineering offers the prospect of revolutionizing human medicine. Burn and wound healing treatment options are very limited in Trinidad and Tobago resulting in a high morbidity/mortality rate of patients. Skin grafts produced from mesenchymal stem cells (MSCs) provide an exciting alternative as an option. This project describes isolation of embryonic MSCs from human umbilical cord blood (UCB-MSCs) and MSCs from bone marrow. We also for the first time in Trinidad and Tobago were able to differentiate UCB-MSCs into fibroblastic lineage cells culture and differentiation into epidermal tissue. Comparison in MSCs obtained will be made between age, ethnicity, and length of gestation to determine correlations. This would provide the basis for using these as a source for skin grafts comparable to allogenic grafts. The results of this project show that human umbilical cord blood is an excellent source of mesenchymal stem cells and that UCB- derived MSCs can be stimulated to differentiate into cells of the epidermal lineage and grown on scaffolding. This preliminary research will be used as a basis for developing skin grafts artificially by differentiation of MSCs into epidermal tissue for application as skin grafts for the treatment of burn victims and for wound healing and/or skin disorders in Trinidad and Tobago.